Environmental Challenges of Present world and its Sustainable Solutions in the light of Seerah - Dr. Sumaira Nawaz (Seerat Studies, 2023)
Environment is one of the concerning issues not only for human being but for each organism that is being discussed today on global level. The circumstances, objects or conditions by which one is surrounded, is an environment. All components of environment either living or non living try to adjust to the environment in which they are living. When any unfavourable change occurs in an environment it is known as environmental degradation. The pollution of the soil, deforestation, contamination of water, air pollution, and the extinction of some species is the phenomena known as environmental challenges and now becoming a global issue and threat for the whole humanity. Actually, Modern man of today’s world has achieved a lot in the form of betterment but is facing severe aggression of environmental crises or challenges. Though the entire world is not free from this danger and its hazards, this problem is more acute in the third world countries by facing twofold crises; crises of development (by Poverty) and crises of environment due to global Change, lack of resources, exploitation of resources and energy supplies. The pursuit of sustainable solutions of these environmental issues has been focus of UN since its inception. In 1972, such issues were highlighted by the world body of UN at Stockholm Sweden for a sustainable solution. The world body also set up their plan for the sustainable development within a peaceful environment to Millennium Development Goal (MDG). This target cannot be achieved while having environmental challenges because sustainable development is not confined to economic growth but it is also ecological sustainability which results in improving the living standards of individual and communities. But still we have not been able to find a sustainable solution to the environmental crises despite of all the modern and technological advancements. A conscious effort for the preservation of nature and natural environment is essential to deal with this problem of enormous magnitude. One way to tackle this problem is to follow the ethical bonds and limitations imposed by religion about environmental protection. Major world religions have some ethical perspective regarding environment and nature traditionally. Unfortunately such type of concern for environment is decreasing in modern society due to greed and materialistic approach. In Islam man and nature are found in a state of unity and harmony, where to plant a tree, to feed and respect an animal, to sustain purity of the water and to remove the hinder from the way, are among the best actions of worship. However, the sustainable development policies can be made environmental friendly by following the Prophetic teachings and by adhering to the ethical responsibilities. In this article, it is purposed how to facilitate environmental friendly conduct through practice of Seerah. This methodological procedure will support environmental friendly behaviours in practice. Subsequently in this context, Prophetic guidance about preventive measures as the solution of environmental challenges is elaborated and discussed in detail.